An open-source musculoskeletal model of the lumbar spine and lower limbs: a validation for movements of the lumbar spine. Issue 12 (6th October 2021) - Favier, C. D.; Finnegan, M. E.; Quest, R. A.; Honeyfield, L.; McGregor, A. H.; Phillips, A. T. M.
Abstract: Musculoskeletal models of the lumbar spine have been developed with varying levels of detail for a wide range of clinical applications. Providing consistency is ensured throughout the modelling approach, these models can be combined with other computational models and be used in predictive modelling studies to investigate bone health deterioration and the associated fracture risk. To provide precise physiological loading conditions for such predictive modelling studies, a new full-body musculoskeletal model including a detailed and consistent representation of the lower limbs and the lumbar spine was developed. The model was assessed against in vivo measurements from the literature for a range of spine movements representative of daily living activities. Comparison between model estimations and electromyography recordings was also made for a range of lifting tasks. This new musculoskeletal model will provide a comprehensive physiological mechanical environment for future predictive finite element modelling studies on bone structural adaptation. It is freely available on https://simtk.org/projects/llsm/ .